Pioneering protein degradation for agricultural applications - Gina L. Morgan; Hamilton Dickson; Breanna Ford; Aleksandra Noras; Steven C. Bremmer; Brian E. Watts; Joseph Pilotte; Ed Anderson; Eric D. Sullivan; Mikayla Stoner; Daniel Ouedraogo; Daniel J. Saltzberg; et al. (Communications Biology)
Abstract As the world of agrochemicals is entering a race for efficient and safe modalities, there is an urgent and specific need for entirely new modes of action. Proteolysis-targeting chimeras (PROTACs) recruit naturally occurring E3 ubiquitin ligases to induce potent and selective degradation of protein targets via the ubiquitin-proteasome system (UPS). Herein, we demonstrate the degradative abilities of the insect VHL (von Hippel-Lindau) E3 ligase, making it the first PROTAC-ready ligase for agriculture applications. In doing so, we developed VHL-recruiting PROTACs capable of degrading fall armyworm (Spodoptera frugiperda) sfBRD3 protein with potencies as high as >80% in Sf9 cells and >60% in larvae. We also successfully designed, optimized, and tested PROTACs that significantly degraded sfWDS protein in both cells and whole organisms. This proof-of-concept study pioneers the use of PROTACs for agricultural applications and establishes this modality as a promising, disruptive alternative to traditional small molecule inhibitors.